Mercury in natural health products as a cause of membranous nephropathy. Issue 2 (2nd April 2020) - Tanner, Stephen; Sharma, Vivek; Jebakumar, Deborah; Narayanan, Mohanram; Rao, Arundhati
Abstract: Membranous nephropathy is a glomerular disease characterized by diffuse subepithelial immune complex deposition along the glomerular basement membrane. It can be both primary and secondary to malignancy and various drugs. An emerging area of concern is heavy metal exposure from use of largely unregulated natural health products. Here we present a case of biopsy-proven membranous nephropathy due to natural health products contaminated with mercury.